Outcomes management practices in tiered school‐based speech–language therapy: A Canadian example. Issue 3 (25th November 2022) - Cahill, Peter T; Ng, Stella; Dix, Leah; Ferro, Mark A; Turkstra, Lyn; Campbell, Wenonah N
Abstract: Background: Measuring, assessing and managing outcomes in school practice environments is difficult due to the complex nature of school communities as well as the recent shift in service‐delivery models towards tiered approaches. In tiered approaches, multiple levels of service are offered to better match students' needs. Each level of service may require different outcomes and management techniques. Research to date on outcomes has focused on measuring outcomes in medical settings, leaving a substantive gap in the literature regarding practice in schools. Aims: The first aim was to explore how school‐based speech–language therapists approached outcomes management as their clinical programmes transitioned to tiered service‐delivery models The second aim was to describe the successes and challenges in outcomes management reported by clinicians in this context. Methods & Procedures: A secondary deductive‐inductive content analysis was performed using qualitative interviews with 24 clinical managers and senior therapists from schools across Ontario, Canada. Using a framework of outcomes measurement, assessment and management in schools based on previous research studies, data were grouped into broad categories deductively, and then the content of each category was further explored using inductive coding. Iterative peer debriefing and reflexive journaling were key strategies to increase the trustworthiness of the results. Findings & Results: Participants reported measuring and qualitatively assessing seven key outcomes for school‐based practice. These included: (1) student progress and achievement, (2) student participation and inclusion in the school community, (3) stakeholder perspectives, (4) 'buy‐in', (5) expanded capacities, (6) responsiveness to needs and (7) accountability to systems. Participants reported more challenges than successes in outcomes management during this transition to tiered services. Challenges were attributed to idiosyncratic organizational barriers, the transition to tiered models and the philosophy of working within the educational system. Conclusions & Implications: School‐based speech–language therapists measure, assess and manage multiple outcomes relevant to school‐based practice in tiered service‐delivery models. Many challenges remain. Solutions to support meaningful, systematic and proactive outcomes management in schools should address the broader set of outcomes relevant to tiered service‐delivery models and the unique practice context of the educational system, while remaining responsive to idiosyncratic organizational factors. Sustained clinical–research collaboration and knowledge exchange is recommended. What This Paper Adds: What is already known on the subject: Systematic, proactive collection and interpretation of outcomes has long been encouraged within speech–language therapy. However, implementing outcomes management in clinical practice remains a substantial challenge. Additionally, research on outcomes to date has focused on medical practice environments, to the exclusion of school‐based practice. What are the potential or actual clinical implications of this work?: Outcomes management is valued in school practice environments; however, the current repertoire of techniques for outcomes management are a poor match for school‐based practice. Clinicians in schools would benefit from the development of contextually relevant, meaningful and feasible outcomes management tools.